The German Syndrome Identification and Information System (DOFONOS) - Leiber, B. (Methods of Information in Medicine, 1975)
This is a report on origin, aims and purpose of a unique service for physicians of all specialties and nationalities.Since 1969, the system DOFONOS, in a largely computerized manner, stores all relevant facts about rare or newly described syndromes about which it gives information upon request free of charge. This information center may also assist in diagnostic identification of patterns. In addition, the information center will develop basic models for computer-aided medical diagnosis. Thereby it attempts to standardize the syndrome and symptom nomenclature in such a way as to be suitable for computer processing. Presently the physician deals with about 30,000 different syndromes the number of whichincreases continuously. This results in an »explosion of information« that shall be relieved by DOFONOS. If a physician needs help in the diagnosis of a disease of unknown type, he may request information about it, provided he supplies an exact description of the symptoms observed.
Keywords: Computer-aided Medical Diagnosis; Syndrome Information Center; Syndrome Identification Center; Symptom Standardization